Revitalizing Ladesta in Gubugklakah: Strengthening Agency and Structure through Organizational Communication - Anang Sujoko; Mega Annisa Insidenta Nuril Huda; Ainun Qisthi Rosyidah; Rachmad Andri Atmoko; Azizun Kurnia Ilahi; Mujibur Rahman Khairul Muluk (Journal of Community Service and Empowerment, 2025)
The Village Tourism Institution (Ladesta) in Gubugklakah was inactive for three years (2021–2024) following a leadership transition, despite its prior national recognition. This dormancy weakened internal coordination, information services, and promotional activities. This article reports on a community service program aimed at reactivating Ladesta by strengthening organizational communication and fortifying institutional structure. Methodological interventions included focus group discussions, the restructuring of management roles, revision of organizational regulations, and capacity building through training in tourism management and digital marketing. Outcomes indicate the establishment of a transitional leadership team, the ratification of revised organizational bylaws, and improved managerial capacity in public services, stakeholder collaboration, and digital promotion. Consequently, these interventions successfully restored organizational functionality and improved member coordination. The study concludes that organizational communication plays a critical role in revitalizing village tourism institutions and sustaining Community-Based Tourism (CBT) management.